Library 2.0 adoption among librarians in academic libraries / Norhidayu Md Yatim - Md Yatim, Norhidayu (2012)
Library 2.0 consists of many applications which are based from the Web 2.0 application and tools. There are many Library 2.0 tools that can be applied in academic libraries and the use of Library 2.0 tools are varying according to its function which can benefit the academic libraries. The purpose of this study is to investigate the perceptions of librarians in academic libraries on Library 2.0 with the focus on their awareness of Library 2.0 concept, use of Library 2.0 tools and services, acceptance toward Library 2.0 application and challenges/barriers of using Library 2.0 applications. The sample selection is using random sampling method. Descriptive statistics using mean, standard deviation and inferential statistics are performed to analyse the data. The result of the study reveals that librarians are familiar with the term Web 2.0 applications adopted in their library and they are aware of the Library 2.0 concept and applications that are commonly used in academic library (overall mean=3.15). Librarians working in comprehensive university are more aware about Library 2.0 concept as compared to librarians working in research university. However, there are no differences between gender, academic qualification, working experience, and age with librarians’ awareness of Library 2.0 concept. The result also reveals that librarians agreed that Library 2.0 applications can provide many opportunities for librarians to reach user and any potential users, it can be used to improve web-based services of academic libraries, and it can enhance library and users interaction (overall mean=4.09).The result reveals that only librarians with different age group have significant difference on their acceptance of the Library 2.0 applications in academic libraries. The study also shows that librarians only used Library 2.0 tools and services on sometimes basis (overall mean=2.98). The result highlights that years of working experience and type of university the librarians served have significant difference regarding the librarians used of Library 2.0 tool and services in academic libraries. The study also found* that the librarians perceived not much challenges/barriers (overall mean=2.82) of using Library 2.0 applications. This study will provide significant feedback on academic librarian’s perception relating to Library 2.0 adoption which is useful for academic library future improvement. Besides, this study will also help library administrator to determine whether the academic librarians need any further training on Library 2.0 applications.